2022
DOI: 10.1371/journal.ppat.1010606
|View full text |Cite
|
Sign up to set email alerts
|

A small molecule that disrupts S. Typhimurium membrane voltage without cell lysis reduces bacterial colonization of mice

Abstract: As pathogenic bacteria become increasingly resistant to antibiotics, antimicrobials with mechanisms of action distinct from current clinical antibiotics are needed. Gram-negative bacteria pose a particular problem because they defend themselves against chemicals with a minimally permeable outer membrane and with efflux pumps. During infection, innate immune defense molecules increase bacterial vulnerability to chemicals by permeabilizing the outer membrane and occupying efflux pumps. Therefore, screens for com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 64 publications
0
11
0
Order By: Relevance
“…All strains tested were unable to grow in the presence of high concentrations of the compound, with values of half minimum inhibitory concentrations (MIC 50 ) ranging from 43 - 93 µM ( Fig 1 A, B ). In contrast, S. Typhimurium with an intact outer membrane grew normally even at 150 µM of D66, a concentration approaching the limit of solubility (11). Thus, bacteria lacking an outer membrane barrier have increased susceptibility to D66 upon out-growth from overnight cultures.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…All strains tested were unable to grow in the presence of high concentrations of the compound, with values of half minimum inhibitory concentrations (MIC 50 ) ranging from 43 - 93 µM ( Fig 1 A, B ). In contrast, S. Typhimurium with an intact outer membrane grew normally even at 150 µM of D66, a concentration approaching the limit of solubility (11). Thus, bacteria lacking an outer membrane barrier have increased susceptibility to D66 upon out-growth from overnight cultures.…”
Section: Resultsmentioning
confidence: 99%
“…D66 inhibits S. Typhimurium survival in macrophages and curbs systemic infection in mice. However, D66 has been challenging to study in broth because it has difficulty passing through the Gram-negative bacterial outer membrane barrier and is expelled by efflux pumps (11). We found that in Gram-positive bacteria, the compound prevented regrowth from stationary phase, suggesting that it can reach a bacterial target(s).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This approach identified molecules that are not antibacterials but that work with host innate immunity to kill bacteria and are therefore anti-infectives. These compounds include efflux pump inhibitors, a stimulator of macrophage autophagy, and two compounds that damage bacterial inner membranes and reduce bacterial tissue load in mice ( 13 17 ). Here, we describe two additional membrane-active, anti-infective compounds, JAV1 and JAV2, which notably have amine groups that are protonatable near pH 6, suggesting compound sequestration within low-pH vesicles, such as the SCV ( 18 , 19 ).…”
Section: Introductionmentioning
confidence: 99%